KARAKTERISTIK PASIEN KISTA OVARIUM DI RSUP SANGLAH DENPASAR PERIODE JANUARI 2019 - DESEMBER 2019 - Dewi, Putu Itta Sandi Lesmana (E-Jurnal Medika Udayana; Vol 11 No 1 (2022): E-Jurnal Medika Udayana, 2022)
ABSTRACT Ovarian cyst is gynecological tumors that are often found in women of childbearing age. The formation of ovarian cyst is influenced by the risk factors such as reproductive age, family history, nulliparous, and hormonal therapy. The purpose of this study is to determine the characteristics of ovarian cyst patients being treated in Sanglah General Hospital. The research design of this study is cross sectional design with retrospective descriptive research. Data were taken by using a total sampling method from the medical records of ovarian cyst patients during the period of January 2019 – December 2019. The research subjects were patients who had been diagnosed with ovarian cyst and recorded in the medical record of Sanglah General Hospital. The patients’ characteristics were described based on age, parity, menstrual status, cyst classification, cyst location, and medical management. The finding of this study is that out of the total sample of 67 medical records of the ovarian cyst patients, there were patients with the majority categories of age at 36-50 years old (37,3%), being dominated by women who had menstruation (67,2%), and mainly found in multiparous women (41,8%). The ovarian cyst was mostly found with benign type (52,2%), which was more common in the right ovary (49,3%). The medical management that was given in Sanglah General Hospital was mostly in the form of operative measures (74,6%). From this study, it can be concluded that ovarian cysts are most often found in women at childbearing age who have experienced menstruation. Ovarian cysts are more common in multiparous women with predominantly benign ovarian cyst type. Ovarian cysts are more common in the right ovary and predominantly performed by surgery. Keywords: Ovarian cyst, characteristics, Sanglah General Hospital